In-vitro Analysis of Antimicrobial Activities of Green Synthesized Silver Oxide Nanoparticles on some Microorganisms found in Open Wound - Abdulmaleek, Rahama Orahachi; Okon, Idongesit Edem; Ndukwe, George Iloegbu; Adamma, Patricia; Ekwumemgbo, E. (Bumi Publikasi Nusantara, 2025)
The main barrier to open wound healing is biofilm formation on the wound by a group of microbes encapsulated in a self-produced extracellular polymeric substance with high resistance to many conventional antimicrobial therapies. There is a need for unique anti-biofilm strategies and antimicrobial agents. This study aimed to investigate the antimicrobial activities of green synthesized silver oxide nanoparticles (Ag2O-NPs) on some bacteria (Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Pseudomonas aeroginosa) and fungi (Candida albican) commonly found in open wound (In-vitro). Ag2O-NPs exhibited considerable zone of inhibition (ZOI) against the test microorganisms. The minimum inhibitory concentration of silver nanoparticles against the bacteria was 3.75 and 15 mg/mL against the bacteria and fungi, respectively. The minimum bactericidal concentration was 7.50 and 15.00 mg/mL for bacteria and fungi, respectively. Green synthesized Ag2O-NPs exhibited some antimicrobial activities, which can aid in wound healing.